A Review of the Therapeutic Potential of Recently Developed G Protein-Biased Kappa Agonists - Mores, Kendall L.; Cummins, Benjamin R.; Cassell, Robert J.; van Rijn, Richard M. (Frontiers in Pharmacology, 2019)
The discovery that morphine is more potent and exhibits fewer side effects in beta-arrestin 2 knockout mice spurred efforts opioids that do not, or weakly, recruit beta-arrestin and whose signaling is primarily transduced via G proteins. Development of such molecules targeting the mu opioid receptor outpaced those targeting the kappa, delta and nociceptin opioid receptors, with the G protein-biased mu opioid agonist oliceridine/TRV130 having completed phase III clinical trials for the treatment of moderate-to-severe acute pain with reduced respiratory depression. Recently however, there has been a sharp increase in the development of novel G protein-biased kappa agonists. It is hypothesized that G protein-biased kappa agonists are analgesic, anti-pruritic and ‘anti-addictive’, but exhibit fewer of the side effects that have thus far limited the clinical development of unbiased kappa opioid agonists. Here we summarize recently discovered G protein-biased kappa agonists, comparing structures, degree of signal bias and preclinical effects. We specifically reviewed nalfurafine, noribogaine, 22-Thiocyanatosalvinorin A (RB-64), mesyl-salvinorin B, 2-(4-(furan-2-ylmethyl)-5-((4-methyl-3-(trifluoromethyl)benzyl)thio)-4H-1,2,4-triazol-3-yl)pyridine (triazole 1.1), 3-(1-(methyl((1-methyl-1H-imidazol-2-yl)methyl)amino)ethyl)phenol (compound 81), 3-(2-((cyclopropylmethyl)(phenethyl)amino)ethyl)phenol (HS666), N-n-butyl- N-phenylethyl-N-3-hydroxyphenylethyl-amine (BPHA), 6-Guanidinonaltrindole (6’GNTI), and collybolide. These agonists encompass a variety of chemical scaffolds and exhibit differences in the potency and efficacy in both their G protein signaling and beta-arrestin recruitment, producing a wide range of signaling bias (bias factors). Thus unsurprisingly, the behavioral responses reported for these agonists are not uniform. Yet, it is our conclusion that the kappa opioid field will benefit tremendously from future studies that compare several biased agonists and correlate the degree of signaling bias to a particular physiological response.